Hidrólise de Lactose por ß-galactosidase de Aspergillus oryzae Imobilizada em Reator de Leito Fixo - Fischer, Janaína (2010)
In this work was studied the lactose s hydrolysis by ß-galactosidase of Aspergillus oryzae immobilized by adsorption and cross-linking with glutaraldehyde, using as carrier the ion exchange resin Duolite A568. The temperature of maximum activity for the immobilized enzyme in the range studied was the 60ºC, with activation energy of 5,32 kcal/mol of lactose, using an initial concentration of lactose from 50 g/L in solution in pH 4,5. The thermal stability of enzyme was studied in the range of 55 to 65C. The thermal deactivation model of first order described significantly the kinetics of thermal deactivation from immobilized enzyme at all temperatures studied, while deactivation model in series in a single step only described the kinetics of thermal deactivation at temperatures of 55 and 57 ºC. The activation energy of thermal deactivation process from ß-galactosidase immobilized was 66,48 kcal/mol with times of half life from 8,9 hours in 55ºC. The immobilized enzyme kept its activity after 90 days of storage, in buffer acetate pH 4,5 in 4 ± 2°C. The influence of lactose concentration and the feed flow in the average rate of reaction from hydrolysis and lactose s conversion in fixed bed reactor, operating in continuous duty, with upflow was studied employing a Central Composite Design (CCD) fixing a temperature of 35 ± 1°C.The best condition for the average rate of reaction from hydrolysis and conversion was: lactose concentration equal to 50 g/L and feed flow equal to 6 mL/min, reaching an average rate of reaction and conversion in 2074 U and 65%, respectively. In order to increase the lactose conversion were performed experiments in two reactors of fixed bed in series, operating in continuous duty, upflow, in the best condition determined by CCD for a fixed bed reactor. The utilization of the second reactor in series increased the lactose conversion in 26%. The immobilized enzyme kept its activity during 30 days of operation in fixed bed reactor, with feed flow of lactose solution 50 g/L equal to 0,3 mL/min, in the room temperature. The determinations of distribution of residence times for the feeding flows in the range of 0,6 to 12 mL/min indicated a non-ideal flow for the column used with formation of short circuits by-pass in the fixed bed reactor.For the study of kinetics in fixed bed reactor, the feeding flows studied were the same of those used in the Residence Time Distribution (RTD) determinations, with lactose 50 g/L in solution at pH 4.5, temperature of 35 ± 1°C, employing the kinetic model of competitive inhibition by galactose. The kinetics of lactose hydrolysis in fixed bed reactor fitted accordingly to the axial dispersion model.